Childhood Sexual Abuse, Spirituality/Religion, Anxiety and Depression in a Jewish Community Sample: the Mediating Role of Religious Coping - Korbman, Miriam D. (Journal of interpersonal violence, 2022)
Childhood sexual abuse (CSA) is a pervasive problem impacting a broad range of mental health outcomes. Previous research has shown that spiritual and religious (S/R) factors both positively and negatively relate to mental health issues among survivors of CSA, but mediating mechanisms of effect are unclear. The present study examined CSA, anxiety, depression, and positive/negative religious coping among 372 Jewish community members with and without CSA histories. Individuals who experienced CSA endorsed significantly higher anxiety and depression as well as negative religious coping than those without CSA. Negative religious coping mediated the relationship between CSA and anxiety and depression. We discuss clinical and social implications of these findings, including the need to address S/R factors in treatment of CSA, especially within religious communities. Further research examining abuser identity, survivors? disclosure experience, and other S/R mediators of effect is warranted.